Intravitreal TSG-6 suppresses laser-induced choroidal neovascularization by inhibiting CCR2(+) monocyte recruitment - Jin Kim, Sang (Sci Rep, 2015)
Choroidal neovascularization (CNV) is the hallmark of wet age-related macular degeneration (AMD), one of the leading causes of blindness in the elderly. Although the pathogenesis of CNV is not clear, a number of studies show that ocular-infiltrating macrophages and inflammation play a critical role in the development of CNV. TNFα-stimulated gene/protein (TSG)-6 is a multifunctional endogenous protein that has anti-inflammatory activities partly by regulating macrophage activation. Therefore, we here investigated the therapeutic potential of TSG-6 in a rat model of CNV induced by laser photocoagulation. Time course analysis showed that the expression of VEGF and pro-inflammatory cytokines in the choroid was up-regulated early after laser injury, and gradually decreased to baseline over 14 days. An intravitreal injection of TSG-6 suppressed the expression of VEGF and pro-inflammatory cytokines including CCL2, and reduced the size of CNV. Also, the number of Iba(+) and CCR2(+) cells including infiltrating macrophages was markedly lower in the CNV lesion of TSG-6-treated eyes. Further analysis identified CCR2(+) CD11b(+) CD11c(+) cells and CCR2(+) CD11b(-)CD11c(+) cells as the cell populations that were increased by laser injury and reduced by TSG-6 treatment. Together, the results demonstrate that TSG-6 inhibits inflammation and CCR2(+) monocyte recruitment into the choroid, and suppresses the development of CNV.